A Course in Mathematical Analysis: Complex Analysis, Measure and Integration, Vol-III - D.J.H. Garling (New Delhi Cambridge University Press, 2018)
School of Mathematics and Natural Science
MIR No.: 198
Order Date: 2024-07-29
Order No: CU/OPEX/LIBRARY/23/2024-25
Received Date: 2024-11-11
Keywords: Mathematics, Comples Analysis